New initiatives for Brazilian aquatic plant data management - Dias Pivari, Marco Otavio; Alves de Mel, Pablo Hendrigo [UNESP]; Souza, Filipe Soares; Stehmann, Joao Renato; Moura Junior, Edson Gomes de; Moreira, Suzana Neves; Pott, Vali Joana; Pott, Arnildo; Lopes, Aline; Chiara Moco, Maria Cecilia; Oliveira, Lukiel dos Santos; Almeida Lins, Alba Lucia de; et al. (Soc Botanica Brasil, 2019)
Initiatives directed at managing information on aquatic plants can support different areas of scientific research, educational practices and political decisions for sustainable management and protection of wetlands and natural resources, as well as reveal knowledge gaps regarding aquatic plants and wetlands. Furthermore, such initiatives can contribute directly to consolidating wetland classification systems in Brazil. The objectives of this work are to present and explore the use of a data repository and online platform created specifically for the management of data on aquatic plants in Brazil. The data repository for aquatic plants was developed to store information on species occurrence records in a standardized form considering: systematics, taxonomy, habit, life form, geographic distribution, hydrographic basin, wetland, bibliographic references and herbarium material. A total of 3,903 records referring to the Southeast Region of Brazil were generated for the data repository. This total encompassed 1,036 species distributed among 132 families and 466 genera. Our results illustrate the diversity of information available regarding aquatic plants, circumscribe this group of species and serve as a source of data about them. Similar databases and electronic infrastructures can be developed for other flora in the future.
Keywords: aquatic macrophytes; biodiversity conservation; data platform; data repository; environmental variables; wetland classification